Você está na página 1de 4

# 1

## 1 Based on the given ordered pairs {(2, 1), (4, 3),

(6, 5), (6, 7)}, an arrow diagram can be drawn as
shown below.
2
4
6
1
3
5
7
9
P
Q
(a) The image of 2 is 1.
(b) The object of 7 is 6.
2 (a) Let g
1
(7) = y
Thus, g(y) = 7
4y 1 = 7
4y = 8
y = 2
g
1
(7) = 2
(b) hg(x)
= h(4x 1)
= (4x 1)
2
3(4x 1) + 5
= 16x
2
8x + 1 12x + 3 + 5
= 16x
2
20x + 9
3
9
28
49
3
5
7
11
Set P Set Q
(a) The range is {3, 7}.

3 and 7 are linked to object(s) but 5
and 11 are not linked to any object.
Therefore, the range is {3, 7}.
(b) The above relation is a many-to-one
relation.

Element 7 in the codomain is
linked to two elements, i.e. 28
and 49 in the domain. Therefore,
it is a many-to-one relation.
4 h : x 2x + m
h(x) = 2x + m
Let h
1
(x) = y
h(y) = x
2y + m = x
y =
x m
2
h
1
(x) =
x m
2
=
x
2

m
2
But it is given that h
1
(x) = 3kx +
3
2
.
Hence, by comparison,
3k =
1
2
k =
1
6
and

m
2
=
3
2
m = 3.
5 (a) hg(x) = 6x 2
h[g(x)] = 6x 2
3g(x) + 1 = 6x 2
3g(x) = 6x 3
g(x) = 2x 1

It is given that h(x) = 3x + 1.
Hence, h[g(x)] = 3g(x) + 1.
Form 4: Chapter 1 (Functions)
SPM Practice
Fully Worked Solutions
Paper 1
2
(b) gh(x) = g(3x + 1)
= 2(3x + 1) 1
= 6x + 1
When gh(x) =
1
3
,
6x + 1 =
1
3
18x + 3 = 1
18x = 2
x =
1
9
6 (a) From the given arrow diagram,
f (2) = 5. Hence, f
1
(5) = 2.
(b) gf (2) = 3

This is a composite function gf (x)
which maps x directly onto z.
7 (a) Let w
1
(x) = z
w(z) = x

6
3 2z
= x

Change the subject of the
formula to z.
6 = x(3 2z)
6 = 3x 2xz
2xz = 3x 6
z =
3x 6
2x
w
1
(x) =
3x 6
2x
, x 0
(b) w
1
h

5
2

= w
1

5
2

+ 3

= w
1
(2)
=
3(2) 6
2(2)
= 3
8 Let n
1
(x) = y
n(y) = x
4y 1 = x
4y = x + 1
y =
x + 1
4
n
1
(x) =
x + 1
4
mn
1
(x) = m

x + 1
4

=

3
8

x + 1
4

5
=
3
2x 3

, x
3
2
9 (a) The relation between set P and set Q is a
many-to-one relation.
(b) The relation can be represented by
f(x) = x
4
.

Function notation
10 m (2) = 7

2 h
h
= 7
2 h = 7h
8h = 2
h =
1
4
11 (a) k = 9
(b) The relation can be represented by
f (x) = x 1.

Function notation
12 f (x) = 9
| x 4| = 9
x 4 = 9
x 4 = 9 or x 4 = 9
x = 13 or x = 5
3
13 g
2
(x) = gg(x)
= g(px + q)
= p(px + q) + q
= p
2
x + pq + q
But it is given that
g
2
(x) = 49x 32.
Hence, by comparison,
p
2
= 49
p = 7 (p > 0)
pq + q = 32
7q + q = 32
8q = 32
q = 4
14 (a) f (x) = 0
| 2x 3| = 0
2x 3 = 0
x =
3
2
k =
3
2
(b) f (4) = | 2(4) 3|
= | 5|
= 5
The range of f (x) is
0 f (x) 5.
15 (a) Let g
1
(6) = y
g(y) = 6
3y + 2 = 6
3y = 4
y =
4
3
g
1
(6) =
4
3
(b) hg(x) = h(3x + 2)
= (3x + 2)
2
2(3x + 2) + 5
= 9x
2
+ 12x + 4 6x 4 + 5
= 9x
2
+ 6x + 5
16 (a) f (6) = 6 + 4
= 10
(b) gf (6) = 24
g(10) = 24
10t 6 = 24
10t = 30
t = 3
17 (a) The object of 2 is 6.
(b) The range is {1, 2, 3}.
18 (a) fg(3) = 4(3) + 8 = 20
(b) fg(x) = 4x + 8
2g(x) + 6 = 4x + 8
2g(x) = 4x + 2
g(x) = 2x + 1
19 (a) f(5) = 5 + 3 = 8
(b) Let f
1
(x) = y
f(y) = x
y + 3 = x
y = x 3
f
1
(x) = x 3
2f
1
(k) = f(5)
2(k 3) = 8
k 3 = 4
k = 7

4
1 (a) f : x 2x 3
f(x) = 2x 3
Let f
1
(x) = y
f(y) = x
2y 3 = x
y =
x + 3
2
f
1
(x) =
x + 3
2
f
1
g(x)
= f
1

x
2
+ 2

x
2

+ 2

+ 3
2

=

x + 4 + 6
2
2
=
x + 10
4
f
1
g : x
x + 10
4
(b) hg : x 2x + 4
hg(x) = 2x + 4
h

x
2
+ 2

= 2x + 4
Let
x
2
+ 2 = u

x
2
= u 2
x = 2u 4
h(u) = 2(2u 4) + 4
= 4u 8 + 4
= 4u 4
h : x 4x 4
Paper 2